2021
DOI: 10.1002/jbt.22775
|View full text |Cite
|
Sign up to set email alerts
|

Role of the BDNF/TrkB/CREB signaling pathway in the cytotoxicity of bisphenol S in SK‐N‐SH cells

Abstract: Bisphenol S (BPS) is associated with neurotoxicity, but its molecular mechanisms are unclear. Our aim was to investigate the role of the brain-derived neurotrophic factor (BDNF)/tyrosine kinase B (TrkB)/cAMP-response element-binding protein (CREB) signaling pathway in BPS-induced cytotoxicity in SK-N-SH cells. The cells were treated with various concentrations of BPS, and cell viability, apoptosis rate, mitochondrial membrane potential (MMP), and the BDNF, cleaved-caspase-3, B-cell lymphoma 2 (Bcl-2), Bcl-2-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Embryonic exposure to low concentrations of BPS caused the damage of neural functionality to persist into adulthood [ 30 ]. BPS could also damage the mitochondrial membrane potential, lead to oxidative stress and decrease the expression of BDNF in SK-N-SH cells [ 14 ]. Oxidative stress has been involved in the debut and/or progress of several neurodegenerative disorders such as Alzheimer disease [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryonic exposure to low concentrations of BPS caused the damage of neural functionality to persist into adulthood [ 30 ]. BPS could also damage the mitochondrial membrane potential, lead to oxidative stress and decrease the expression of BDNF in SK-N-SH cells [ 14 ]. Oxidative stress has been involved in the debut and/or progress of several neurodegenerative disorders such as Alzheimer disease [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In male mice, postnatal exposure to 50 µg/kg or 10 mg/kg BPS has harmful implications for reproductive function, including low sperm concentration, motility and steroid hormone levels [ 12 ]. In addition, many studies have shown that BPS could damage nerve cells in vitro [ 13 , 14 ], and change animal behaviour and induce neurotoxicity [ 15 ]. For example, prenatal exposure to BPS reduced fertility and changed maternal behaviour in female rats [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…**p < .01 compared with the control group. Bar = 25 μm membrane and opens mitochondrial permeability transition pore (mPTP), which results in loss of MMP, outer membrane rupture and a series of apoptotic responses (He et al, 2021;. To confirm mitochondrial alterations in the process of apoptotic cell death caused by BPS, we observed the levels of MMP and morphological changes in mitochondria in MLO-Y4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the degradation of nuclear DNA, mitochondrial impairment has been identified to be involved in apoptosis (Yang et al, 2019; Yang et al, 2019). BPS exposure to human neuroblastoma cells, TM3 mouse Leydig cells and SK‐N‐SH cells targets the inner mitochondrial membrane and opens mitochondrial permeability transition pore (mPTP), which results in loss of MMP, outer membrane rupture and a series of apoptotic responses (He et al, 2021; Wang et al, 2021; Wang et al, 2021; Zhang et al, 2022). To confirm mitochondrial alterations in the process of apoptotic cell death caused by BPS, we observed the levels of MMP and morphological changes in mitochondria in MLO‐Y4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF), a well-known neurotrophic protein of the nervous system, is involved in neuronal survival, growth, differentiation, and maturation [ 24 , 25 ] through the tropomyosin receptor kinase B (TrkB) receptor binding and subsequent CREB phosphorylation [ 26 , 27 , 28 , 29 ]. The BDNF/TrkB/CREB pathway is known to be involved in antidepressant, anti-apoptotic, and antioxidative mechanisms [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%